Bildschirmlesegeräte: aktueller Stellenwert und Hinweise zu Anpassung und Verordnung - Rohrschneider, Klaus; Bayer, Yasmin; Brill, B. (Der Ophthalmologe, 2018)
Closed-circuit television systems (CCTVs) have become an indispensable tool in rehabilitating low vision patients. Compared to optical visual aids, apart from providing maximum magnification these devices have the additional advantage of improved contrast sensitivity and an enlarged field of view. They are often the only visual aid enabling patients to regain reading ability. Our data reflect a decrease in the number of prescriptions caused by improved counseling of low-vision patients. Any prescription of reading aids must be preceded by comprehensive testing and counseling. More recent developments, such as electronic magnifiers are becoming increasingly more important but they are no substitute for CCTV.
First online: 22 December 2017
Gesehen am 10.04.2019